2023
DOI: 10.1128/jvi.01528-22
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr Virus Glycoprotein BDLF2 Is Essential for Efficient Viral Spread in Stratified Epithelium

Abstract: The ubiquitous herpesvirus Epstein-Barr virus (EBV) is associated with cancers of B lymphocytes and epithelial cells and is primarily transmitted in saliva. While several models exist for analyzing the life cycle of EBV in B lymphocytes, models of EBV infection in the epithelium have more recently been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…This virus contains seven structural proteins, which have fundamental roles for the virus; for example, BFRF3 is associated with the assembly of the viral capsid [166,167]. Several glycoproteins have diverse functions, such as the fusion of the viral envelope on the host cell, viral propagation, and the disruption of the antiviral response [168][169][170][171]. Additionally, this virus presents tegument proteins, whose functions are varied.…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…This virus contains seven structural proteins, which have fundamental roles for the virus; for example, BFRF3 is associated with the assembly of the viral capsid [166,167]. Several glycoproteins have diverse functions, such as the fusion of the viral envelope on the host cell, viral propagation, and the disruption of the antiviral response [168][169][170][171]. Additionally, this virus presents tegument proteins, whose functions are varied.…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…However, no experimental data currently supports a role for any of these viral proteins in transmembrane transport. Instead, EBV BMRF2 can change cellular morphology by modulating the actin cytoskeleton 45 and is essential for efficient cell-cell spread 46 . UL43 colocalizes with proteins involved in membrane fusion and potentially interacts with the gN/gM complex 47 , which is engaged in syncytia formation 48 .…”
Section: Structural Similarity Search Of Human Herpesvirus Protein Mo...mentioning
confidence: 99%
“…The authors infected organotypic cultures with wild type viruses and observed focus of infection represented by numerous clusters of infected cells compared with cells infected with lack of BDLF2 viruses, which displayed fewer infected and isolated cells. This suggested a significant role of BDLF2 in intercellular viral spread [ 75 ]. Sciver et al seeded NOKs-Akata cells over-expressing ΔNp63ɑ onto collagen-treated membranes in ALI culture conditions.…”
Section: Ali Cultures For Ebv/hpv Biology and Cancer Initiationmentioning
confidence: 99%